Phase I dose-escalation study of the safety, pharmacokinetics, and pharmacodynamics of the MEK inhibitor RO4987655 (CH4987655) in patients with advanced solid tumors. - Leijen, S; Middleton, MR; Tresca, P; Kraeber-Bodéré, F; Dieras, V; Scheulen, M; Gupta, A; Lopez-Valverde, V; Xu, Z; Rueger, R; Tessier, J; Shochat, E; et al. (2012)
PURPOSE: This phase I study of the mitogen-activated protein/extracellular signal-regulated kinase inhibitor RO4987655 (CH4987655) assessed its maximum tolerated dose (MTD), dose-limiting toxicities (DLT), safety, pharmacokinetic/pharmacodynamic profile, and antitumor activity in patients with advanced solid tumors. PATIENTS AND METHODS: An initial dose escalation was conducted using a once-daily dosing schedule, with oral RO4987655 administered at doses of 1.0 to 2.5 mg once daily over 28 consecutive days in 4-week cycles. Doses were then escalated from 3.0 to 21.0 mg [total daily dose (TDD)] using a twice-daily dosing schedule. RESULTS: Forty-nine patients were enrolled. DLTs were blurred vision (n = 1) and elevated creatine phosphokinase (n = 3). The MTD was 8.5 mg twice daily (TDD, 17.0 mg). Rash-related toxicity (91.8%) and gastrointestinal disorders (69.4%) were the most frequent adverse events. The pharmacokinetic profile of RO4987655 showed dose linearity and a half-life of approximately 4 hours. At the MTD, target inhibition, assessed by suppression of extracellular signal-regulated kinase phosphorylation in peripheral blood mononuclear cells, was high (mean 75%) and sustained (90% of time >IC(50)). Of the patients evaluable for response, clinical benefit was seen in 21.1%, including two partial responses (one confirmed and one unconfirmed). 79.4% of patients showed a reduction in fluorodeoxyglucose uptake by positron emission tomography between baseline and day 15. CONCLUSION: In this population of heavily pretreated patients, oral RO4987655 showed manageable toxicity, a favorable pharmacokinetics/pharmacodynamics profile, and promising preliminary antitumor activity, which has been further investigated in specific populations of patients with RAS and/or RAF mutation driven tumors.